38. Sommarset og Kistholmbukta: Avskrevne lokaliteter - Krokmyrdal, Tor Ketil; Oppvang, Janne (Tromura, 2025)
Both Kistholmbukta and Sommeret must be considered as areas without traces of cultural heritage.Whether this was due to a registration error or incorrect coordinates being provided is unknown. A search for cultural heritage was conducted in a larger area around the sites, but this also yielded no results.
Keywords: Stone foundation house; Dismissed